Attracting Talent: The Role of Social Media and Employer Attractiveness on Job Pursuit Intention Mediated by Corporate Reputation in E-commerce Companies of Indonesia - Anthony Julius Tedjokumolo; Benedictus Jevon Tjoanda (iBuss Management, 2020)
The rapid growth of Indonesia’s digital economy has been mainly driven by the e- commerce segment which was predicted to have a bright future outlook. However, this growth cannot be sustained without the support of digital talent. This situation raises concern, especially because Indonesia is experiencing a deficit of digital talent. The e-commerce companies have to fiercely compete to attract the digital talent they need. Therefore, the main purpose of this research is to understand potential employees’ perceptions of employers and their job pursuit intention through the mediation effect of corporate reputation. The object of this research is Shopee and Tokopedia. In the analysis, 117 data of final year undergraduate students in Information Technology related programs are analyzed with multiple linear regression with path analysis in IBM SPSS 26, and mediation test using Bootstrapping in PROCESS 3.5. Within 95% confidence level, the findings suggest that corporate reputation complementary mediates the relationship of social value and development value to job pursuit intention. While economic value and company-generated social media communication each have an indirect-only mediation to job pursuit intention when mediated by corporate reputation.Keywords: Employer Attractiveness, Company-Generated Social MediaCommunication, Corporate Reputation, Job Pursuit Intention